The Budgetary Chessboard: Strategies and Challenges in North Maluku Province's Fiscal Landscape - Muhammad Hi Hasan; Budiyanto Budiyanto; Akhmad Riduwan (Cita Konsultindo Research Center, 2024)
This study examines how certain factors moderate opportunistic budgeting behavior in North Maluku Province by focusing on achieving strategic marketing outcomes. Financial data from the past decade across ten districts/cities, including capital expenditure, regional original revenue, general allocation fund, remaining over-budget calculations, and opportunistic behavior of budgeting, were analyzed using the Moderating Analysis Regression (MRA) model. The findings of this study are as follows: (1) Regional Original revenue significantly impacts the opportunistic behavior of budgeting within districts/cities in North Maluku Province; (2) general allocation funds significantly influence the opportunistic behavior of budgeting within districts/cities in North Maluku Province; (3) the remaining over-budget calculations do not significantly affect the opportunistic behavior of budgeting within districts/cities in North Maluku Province; (4) capital expenditure does not moderate the relationship between Regional Original income and the opportunistic behavior of budgeting in districts/cities in North Maluku Province; (5) capital expenditure does not moderate the relationship between general allocation funds and the opportunistic behavior of budgeting in districts/cities in North Maluku Province; and (6) capital expenditure does not moderate the relationship between the remaining over-budget calculations and the opportunistic behavior of budgeting in districts/cities in North Maluku Province.